KENDALA YANG DIHADAPI GURU TUNAGRAHITA DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH LUAR BIASA (SLB) ABC MANDARA KENDARI - Desti Desti; Damsid Damsid; Ratna Supiyah (Universitas Halu Oleo, 2023)
The teacher is someone who gives knowledge to students. Teachers in the view of society are those who carry out education in certain places, not necessarily in formal educational institutions, but also in mosques, mosques, prayer rooms, at home, and so on. The purpose of this study was to find out the obstacles faced by mentally retarded teachers in the teaching and learning process at the ABC Mandara Kendari Special School (SLB). This study uses a qualitative descriptive method. Determination of informants in this study using a purposive sampling method. The data sources used in this study are primary data and secondary data. The data collection techniques in this study used interview, observation and documentation techniques. Data analysis techniques in this study used data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the obstacles faced by mentally retarded teachers in the teaching and learning process at the ABC Mandara Kendari Special School (SLB), namely students who are less focused when participating in the learning process in the classroom are the cause of their lack of focus because they only think about things about playing. as well as their intellectual delays and their moods, which vary every day. and special infrastructure for children with special needs are also obstacles for teachers in implementing the learning process in class. After discovering what obstacles the teacher faces in the learning process the teacher has a strategy for dealing with this. The teacher's strategy for dealing with students who are less focused while studying is by providing a method of playing while learning or creating a more enjoyable learning atmosphere. The teacher's strategy in dealing with students' different moods is by presenting interesting and creative material and attracting their attention and also seducing them until their mood improves and they want to re-follow the learning process in the classroom. The teacher's strategy in handling the lack of facilities when teaching is by overcoming it, namely by using cellphones and laptops internet media so that they are not left behind in learning because books are still very limited